2021
DOI: 10.3390/ma14216605
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Aggregates from Construction and Demolition Waste in the Manufacture of Urban Pavements

Abstract: Construction and Demolition Waste (CDW) is among the largest waste streams in the world. Therefore, within the Circular Economy concept, there is a growing interest in its reuse. The purpose of this work was to study the use of recycled aggregates (RAs) obtained by a specific separation method from CDW, replacing natural aggregates (NAs) in the manufacture of precast concrete elements, such as kerbstones and paver blocks. The physical and technological properties of precast products formulated with RAs were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
(57 reference statements)
3
16
0
Order By: Relevance
“…This result confirms what was observed in the literature review [34,36,65]. Generally, recycled CDWs almost have higher water absorption values than natural aggregates that have water absorption (WA) values between 0.5% and 1.5% [35,66,67]. However, these higher WA values of the recycled CDWs aggregates could be attributed to their lower density and therefore higher porosity compared to natural aggregates [64].…”
Section: Fig 3 Scanning Electron Microscopy (Sem) Images Of Recycled ...supporting
confidence: 89%
See 1 more Smart Citation
“…This result confirms what was observed in the literature review [34,36,65]. Generally, recycled CDWs almost have higher water absorption values than natural aggregates that have water absorption (WA) values between 0.5% and 1.5% [35,66,67]. However, these higher WA values of the recycled CDWs aggregates could be attributed to their lower density and therefore higher porosity compared to natural aggregates [64].…”
Section: Fig 3 Scanning Electron Microscopy (Sem) Images Of Recycled ...supporting
confidence: 89%
“…However, these values are acceptable and are in accordance with the requirements of the EN 13242 standard [48]. It was reported that the recycled aggregates has a significantly higher LA and MDE coefficients than the natural ones [66,67]. This can be probably due to the presence of old cement paste surrounding natural aggregates and ceramic materials, etc.…”
Section: Fig 3 Scanning Electron Microscopy (Sem) Images Of Recycled ...supporting
confidence: 73%
“…In recent years, the sustainable engineering of construction development has increased; therefore, several researchers have doubled their efforts toward projects where the mean objective is to analyze the feasibility of recycling construction and demolition waste (CDW) as new building materials, focusing on mechanical behavior, durability, and environmental impact [ 1 , 2 , 3 , 4 , 5 , 6 ]. One way these residues can be used is as partial substitutes for natural aggregates (NAs) in concrete and mortar mixes, such as recycled coarse aggregates (RCAs) and recycled fine aggregates (RFAs) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] One of the strategic lines of the European Union policies aims to ensure the "Circular Economy" through the efficient use of raw materials and residues and the generation of clean energy. For that, policies on waste management must be directed in respect of the hierarchy of 4Rs established by the normative: reduction, reuse, recycle, and recovery [5].…”
Section: Introductionmentioning
confidence: 99%